2000
DOI: 10.1038/emm.2000.29
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide induces rat peritoneal mast cell activation by cGMP-independent and calcium uptake-dependent mechanism

Abstract: Atrial natriuretic peptide (ANP), a 28 amino acid basic polypeptide, is known to induce histamine release from human and rat mast cells in vitro and cause a wheel formation in rat skin. However, cellular events associated with histamine release are not clearly understood. In this study, we have examined the calcium flux and cGMP formation associated with histamine release in the ANP-treated mast cells. ANP, in vitro, induced mast cell degranulation and histamine release in a dose-dependent manner. ANP also ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Contradicting our results, it was reported that ANP itself can activate mast cells isolated from peritoneum or placenta, with the former being mediated via a GC-A/cGMP-independent pathway. 37,38 In contrast, ANP does not induce degranulation of isolated rodent cardiac mast cells. 39 Therefore, it seems that there is variability in the actions of ANP on mast cells isolated from different organs.…”
Section: Discussionmentioning
confidence: 99%
“…Contradicting our results, it was reported that ANP itself can activate mast cells isolated from peritoneum or placenta, with the former being mediated via a GC-A/cGMP-independent pathway. 37,38 In contrast, ANP does not induce degranulation of isolated rodent cardiac mast cells. 39 Therefore, it seems that there is variability in the actions of ANP on mast cells isolated from different organs.…”
Section: Discussionmentioning
confidence: 99%
“…7,39 Also, ANP induces mast cells to release histamine, an important mediator of allergic inflammation. 40,41 ANP acts on epithelial cells to produce TGF-b 1 , which is involved in the genesis of pulmonary fibrosis, a characteristic of remodeled lung. ANP enhances human NK T cells, 42 which are crucial to the development of airway hyperreactivity.…”
Section: Development Of the Immune System And The Pathogenesis Of Asthmamentioning
confidence: 99%
“…It was concluded that this elevation in the myocardial natriuretic system was an adaptational, autocrine/paracrine response responsible for regulating cardiac remodeling (1,17,19,22,26). ANP, which has been shown to cause degranulation in noncardiac mast cells (10,29,39), was originally identified as a member of a family of three separate peptide neurohormones, Fig. 2.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic volume overload (CVO) has been shown to induce rapid expression of atrial natriuretic peptide (ANP) mRNA and protein in cardiac tissue, as well as natriuretic peptide receptors (NPRs) (3,22,31,35). Furthermore, ANP has been shown to cause degranulation in noncardiac mast cells (10,29,39). However, it is not known whether ANP activates cardiac mast cells.…”
mentioning
confidence: 99%